The Role of Education in Addressing the Challenges of Women’s Political Empowerment: A Reading of Societal Challenges and Solutions - علي سجى عادل (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
Education fulfills a variety of essential roles, with two of its principal functions being the empowerment of individuals and the cultivation of skills required to navigate diverse circumstances. These functions are intrinsically linked to the dissemination of knowledge, skills, and understanding across various societal groups, alongside fostering behaviors that enable individuals to act effectively and make informed decisions. The second key role of education is socialization, which involves helping individuals integrate into societies and participate in various social, cultural, political, professional, or religious practices and traditions through the learning process. In some cases, attention is directed towards a specific interest such as instilling the values ​​of citizenship and democracy and ways of working and being in certain professional societies. Education serves as a vital tool for socialization, helping individuals adopt established practices and behaviors, thereby ensuring the preservation of culture and traditions. Beyond its role in fostering social cohesion and integration, education also empowers women by shaping their roles within their communities. This interconnected relationship between education and women stands as a cornerstone for driving sustainable development and cultivating resilient societies. Promoting women’s education is widely regarded as a pivotal step toward expanding economic and social opportunities. It plays a crucial role in advancing gender equality within the educational landscape.